Geometrical potential and nanofiber membrane's highly selective adsorption property. Issue 5 (July 2019) - Tian, Dan; Li, Xiao-Xia; He, Ji-Huan
The definition of a nanofiber is discussed, and the history of the development of bubble electrospinning is briefly elucidated, its main properties are emphasized, and the morphology of its products is summarized. A geometrical interpretation of the nanofiber membrane's adsorption is given as a natural intrinsic property of the geometrical potential of nanoscale structure. Nano-effect, Casimir effect, capillary effect, Earth's gravity difference, Newton's gravity, and lotus leaf's highly selective repulsion property can all be interpreted using the geometrical potential or boundary-induced force.